Epidermoid carcinoma of the hypopharynx in a child: a rare case report - Omar, Wydadi; Hicham, Lyoubi; Adil, Lekhbal; Lah, Abada R.; Sam, Rouadi; Mohamed, Roubal; Mohamed, Mahtar (International Journal of Scientific Reports, 2020)
Epidermoid carcinoma is a frequent tumor in the upper aerodiodestive tracts, and depending on its location and tumor, nodes, metastases (TNM) stage, its therapy and prognosis vary enormously. Its location in the hypopharynx is rare, and in children or young adolescents, this location is extremely rare; The incriminated causes and the pathophysiology of the development of these tumors at this age remain a mystery. We present the case of a young patient of 13 years old, followed for squamous cell carcinoma of the right piriform sinus, with contralateral synchronous tonsil localization, and right lateral cervical lymphadenopathy fixed at 5 cm. In the absence of existing guidelines on the management of this type of location at this age, a multi-disciplinary meeting was necessary to decide on the management of this difficult case at this age.